Human neutrophils employ the myeloperoxidase-hydrogen peroxide-chloride system to convert hydroxy-amino acids into glycolaldehyde, 2-hydroxypropanal, and acrolein. A mechanism for the generation of highly reactive alpha-hydroxy and alpha,beta-unsaturated aldehydes by phagocytes at sites of inflammation. - Anderson, M M; Hazen, S L; Hsu, F F; Heinecke, J W (The Journal of Clinical Investigation, 1997)
Reactive aldehydes derived from reducing sugars and lipid peroxidation play a critical role in the formation of advanced glycation end (AGE) products and oxidative tissue damage. We have recently proposed another mechanism for aldehyde generation at sites of inflammation that involves myeloperoxidase, a heme enzyme secreted by activated phagocytes. We now demonstrate that human neutrophils employ the myeloperoxidase-H202-chloride system to produce alpha-hydroxy and alpha,beta-unsaturated aldehydes from hydroxy-amino acids in high yield. Identities of the aldehydes were established using mass spectrometry and high performance liquid chromatography. Activated neutrophils converted L-serine to glycolaldehyde, an alpha-hydroxyaldehyde which mediates protein cross-linking and formation of Nepsilon-(carboxymethyl)lysine, an AGE product. L-Threonine was similarly oxidized to 2-hydroxypropanal and its dehydration product, acrolein, an extremely reactive alpha,beta-unsaturated aldehyde which alkylates proteins and nucleic acids. Aldehyde generation required neutrophil activation and a free hydroxy-amino acid; it was inhibited by catalase and heme poisons, implicating H202 and myeloperoxidase in the cellular reaction. Aldehyde production by purified myeloperoxidase required H202 and chloride, and was mimicked by reagent hypochlorous acid (HOCl) in the absence of enzyme, suggesting that the reaction pathway involves a chlorinated intermediate. Collectively, these results indicate that the myeloperoxidase-H202-chloride system of phagocytes converts free hydroxy-amino acids into highly reactive alpha-hydroxy and alpha,beta-unsaturated aldehydes. The generation of glycolaldehyde, 2-hydroxypropanal, and acrolein by activated phagocytes may thus play a role in AGE product formation and tissue damage at sites of inflammation.